A Educação escolar indígena entre os Wassu-Cocal: algumas pistas sobre a concepção da educação escolar a partir de seus professores - Pereira, Jéssika Danielle dos Santos (2014)
The present work analyzes the construction of the concept of Indigenous school education between the Wassu-Cocal, especially among the indigenous tutors and leaders. The Wassu people-Cocal is located in the zona da mata alagoana the 84 km from Maceió and 16 km from the city of Joaquim Gomes. We understand that the Indigenous Education refers to the processes of production and transmission of indigenous peoples ' own knowledge and that every nation has its particular way of doing it. However, we point out that in the process of construction of the design of this education are involved multiple social actors. In addition to the teachers, are entered into this process the students, families, the community and the State itself. O last through official documents, including the Constitution of 1988, the National curricular parameters (PCN/1997), the law of Guidelines and Bases for national education (LDBEN/1996), the National Education Plan (PNE/2001-2010; PNE/2011-2020) and, in the specific case of Wassu-Cocal, also the education of Alagoas State plan (ESSP/2006-2015). To help us understand the relationships that these agents between you and the way the design of Indigenous school education is being built, and how it connects to the cultural context in which this educational practice is embedded, we adopt the Ethnography as methodological instrument. The field research was held from 03 May-06 December 2013, together with the teachers/the indigenous Indian State school José Maximum. Research has shown us that the design of the Indigenous school education between the Wassu-Cocal is constructed from the interrelation of the agents, by seizing and spread ethnoknowledge construction, built in various spaces in the village. Is construction represents, in this sense, the ethnic identity of the people Wassu-Cocal, which should be full by the school, a place of (re) affirmation and maintain your way of being. The survey also pointed out that the inclusion of indigenous teachers at the top level have modified the teaching practice and the social dynamics of the village; their actions have driven the agents involved in the school to recognize in this fight for a school and indigenous education.